Corn poppy (Papaver rhoeas L.) resistance to ALS inhibiting and 2,4-D herbicides in Moroccan and Tunisian rainfed wheat fields - Zakia El-Mastouri; Pavlína Košnarová; Kateřina Hamouzová; Ezzedine Alimi; Josef Soukup (Plant, Soil and Environment, 2025)
Corn poppy (Papaver rhoeas L.) is one of the most problematic weed species, mainly in rainfed Moroccan and Tunisian cereal crops. The overuse of acetolactate synthase (ALS) inhibiting and/or auxinic herbicides led to the spread of corn poppies resistant to both chemical families in this region. In order to identify and understand the selection drivers of resistance, appropriate characterisation of the resistance profile is necessary. Two experiments were carried out: biological sensitivity tests with ALS inhibiting herbicides (tribenuron-methyl and florasulam) and auxinic herbicides (2,4-d) were carried out with populations sampled in the field where the herbicide failure was observed. Bioassay tests confirmed resistance in all studied populations with an average frequency of 75.13, 30.81, 33.17 and 11.52% with tribenuron, florasulam, 2,4-d and florasulam + 2,4-d, respectively. Corn poppy sampled from both countries exhibited similar frequencies within populations for each tested herbicide. The molecular analysis was conducted with next-generation sequencing (Illumina), allowing massive, precise and rapid sequencing regions of the ALS gene carrying resistance codons. Using this technology, ALS mutant alleles were found in all populations at frequencies ranging from 1.4% to 63.3%, with an average of 16.7%. This study highlights the need to elucidate resistance mechanisms to understand herbicide responses and develop effective strategies for managing resistant corn poppy in rainfed cereals as an essential step to maintain the effectiveness of these molecules as long as possible.